Investigation of the contribution of bioaerosol loading to indoor PM pollution on university campus in Singapore - Lee, Brandon Jia Hao (Nanyang Technological University, 2022)
Indoor bioaerosol pollution may cause allergies and diseases and with people spending up to 90% of their time indoors, the indoor bioaerosol loading on a university campus was investigated to quantify indoor air pollution and develop mitigation strategies. Culture-based air sampling and optical particle counter methods were used to investigate particle mass and pathogenic microorganisms concentration namely bacteria and fungi. The study found that median fungi concentration was higher than bacteria concentration with a high prevalence of both bacteria and fungi concentration in fine particles smaller than 1.1um. Particle mass was found to be significantly higher in fine particles between 0.25-0.45um as compared to larger particles. Fine particles could be mitigated safely for occupants with an electrostatic precipitator and future work could expound on elevated fungi concentrations in an indoor environment and fine particle mitigation strategies.